2020
DOI: 10.1109/access.2020.3023746
|View full text |Cite
|
Sign up to set email alerts
|

Human Segmentation Based on Compressed Deep Convolutional Neural Network

Abstract: Most semantic segmentation models based on deep convolutional neural network (CNN) typically require a large number of weight parameters, high hardware resources for storage and computation. Moreover, redesigning a compact network suffers from some training problems, such as under-fitting. A human segmentation algorithm is proposed based on compressed deep CNN to optimize the convolution layers and filters. PSPNet-50 is fine-tuned on the human segmentation dataset to obtain the human segmentation model with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Liang et al [14] introduced a segmentation method called the TriSeNet. Unlike the U-Net, the whole network in this method is composed of three different network paths to extract the high-dimensional spatial features, high-level semantic features and detailed boundary features.…”
Section: Segmentationmentioning
confidence: 99%
“…Liang et al [14] introduced a segmentation method called the TriSeNet. Unlike the U-Net, the whole network in this method is composed of three different network paths to extract the high-dimensional spatial features, high-level semantic features and detailed boundary features.…”
Section: Segmentationmentioning
confidence: 99%
“…To optimize the convolution layer and filter, J Miao's team proposed a human body segmentation algorithm based on the compressed depth Convolutional neural network, and adopted a two-stage global filter level pruning strategy. The results showed that the segmentation speed of this method is increased by 2.4 times [6]. Chu J et al proposed an instance segmentation method that integrates non maximum suppression algorithms for semantic segmentation of bounding boxes returned by detectors.…”
Section: Related Workmentioning
confidence: 99%
“…ReLU activates neurons then the gradient provides all times the high value. ReLU, f(n) is defined as MAX(0,n) (Miao J. et al, 2020, Feng S. et al, 2021, Zhou Y. et al, 2019& Rossinelli D. et al, 2020. Algorithm2 describes the non-ROI compression of the medical image using CNN.…”
Section: Convolution Neural Network Based Compressionmentioning
confidence: 99%